Performance of elite maize genotypes under selected sustainable intensification options in Kenya - Rusinamhodzi, Leonard; Makumbi, Dan; Njeru, J.M.; Kanampiu, F.K. (Elsevier, 2020)
Combining different cropping and tillage systems with different genotypes across several cropping seasons can reveal opportunities for sustainable intensification (SI). The objective of this study was to assess the performance of six maize genotypes under intercropping with conservation tillage (no-till) – two promising options for SI. The experiment was carried out over three years (or six cropping seasons) at Kiboko Research Station, Kenya with sole cropping and mouldboard ploughing as baseline production systems. Results showed that maize genotypes and cropping systems had a significant effect on yield, but the effect of tillage was not significant. Moreover, there was no significant interactive effects of the tested factors on maize yield. The maize genotype CKH10085 had the highest yield of 7.7 t ha−1 under sole cropping yet it also recorded the largest yield penalty due to intercropping of 1.1 t ha−1. On the other hand, genotype CKH10717 maintained the same average yield of 7.1 t ha−1 in both conventional and conservation tillage systems. The commercial genotype genotype CKH10080 and CKH08051 were more stable than the other experimental genotypes under the variable growing and management conditions. These two genotypes are of intermediate maturity and drought tolerance, two critical attributes to improved maize production. Intercropping reduced maize yields due to increased competition, for example the overall yield of sole cropping was 7.1 t ha-1 compared with 6.4 t ha-1 under intercropping; representing an overall yield penalty of 0.7 t ha-1. The differences in performance of maize genotypes revealed opportunities to deploy genotypes to reduce risk or maximize yield, depending on the biophysical circumstances and the production objective of the farmer.